2011
DOI: 10.1016/j.biocon.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Plant community functional shifts in response to livestock grazing in intermountain depressional wetlands in British Columbia, Canada

Abstract: Wetlands are ecologically and economically important ecosystems with high conservation value. Although wetland vegetation is strongly determined by abiotic factors, grazing disturbance may also be an important influence on this community. We evaluated the effects of livestock grazing on wetland vegetation in marsh and wet meadow zones in intermountain depressional wetlands in the southern interior of British Columbia, Canada. We sampled marshes and wet meadows in 36 wetlands along a grazing intensity gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 51 publications
2
28
1
Order By: Relevance
“…Using various grazing exclusion trials in grasslands in southeastern Australia, Mavromihalis et al () recorded an overall loss of plant species richness coupled with an increase in herbage mass with complete exclusion of sheep but found little consistent changes in native species composition with other seasonal grazing exclusion treatments. A study of depressional wetlands in British Columbia, Canada, found differential responses of the plant community to grazing intensity depending on the type of wetland with a general increase in annual forbs and decrease in perennial herbaceous species with increasing intensity (Jones et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Using various grazing exclusion trials in grasslands in southeastern Australia, Mavromihalis et al () recorded an overall loss of plant species richness coupled with an increase in herbage mass with complete exclusion of sheep but found little consistent changes in native species composition with other seasonal grazing exclusion treatments. A study of depressional wetlands in British Columbia, Canada, found differential responses of the plant community to grazing intensity depending on the type of wetland with a general increase in annual forbs and decrease in perennial herbaceous species with increasing intensity (Jones et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Trampling by livestock selects for annuals, forbs and short species (e.g. Jones, Fraser & Curtis ), has negative effects on tall palatable species (Boughton et al . ; Jones, Fraser & Curtis ) and can lead to shrub invasion (Middleton ).…”
Section: Introductionmentioning
confidence: 99%
“…The subalpine vegetation metrics negatively influenced by grazing disturbance in our study have often been shown to be affected in other, more intensively grazed, environments [53], [67][69]. Effects on bare ground and litter are sufficiently established that these characteristics have been used as proxies for grazing intensity and/or as manipulated variables used in experimental assessments of grazing pressure [52], [53], [70].…”
Section: Discussionmentioning
confidence: 64%
“…Effects on bare ground and litter are sufficiently established that these characteristics have been used as proxies for grazing intensity and/or as manipulated variables used in experimental assessments of grazing pressure [52], [53], [70]. Litter removal can cause shifts in soil moisture [70] which could, along with direct pressure from trampling, mediate some of the observed increases in soil strength (in the form of compaction) on our sites.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation